Evaluation of digital and optical refractometers for assessing failure of transfer of passive immunity in Chianina beef–suckler calves reared in Umbria. Issue 1 (1st January 2021) - Pisello, Lorenzo; Boccardo, Antonio; Forte, Claudio; Pravettoni, Davide; D'Avino, Nicoletta; Passamonti, Fabrizio; Rueca, Fabrizio
Abstract: There are few published data on the accurate on-farm diagnosis of failure of transfer of passive immunity (FTPI) in beef–suckler calves. This observational study aimed to evaluate the diagnostic performance and differences among four types of refractometers for assessing FTPI in Chianina beef–suckler calves. Blood samples were collected from 85 Chianina calves aged 2–7 days. The serum immunoglobulin G (IgG) concentration was measured using radial immunodiffusion (RID), digital and optical serum total protein (STP) refractometers, and digital and optical serum refractometers. The diagnostic performance of the refractometers was determined based on the serum IgG threshold of 16 g/L (measured by RID). A receiver operating characteristic (ROC) curve was used to identify the optimal cutoff values for all refractometers. The RID IgG concentration was positively correlated with all four refractometers (correlation coefficient: 0.75–0.84). ROC analysis yielded optimal cutoff values for predicting FTPI of 51 g/L (sensitivity (Se)=0.63 and specificity (Sp)=0.96) and 52 g/L (Se = 0.69 and Sp = 0.90) for the digital and optical STP refractometers, respectively. At the threshold of 8.3% Brix, the Se and Sp were 0.66 and 0.92 for the optical Brix and 0.77 and 0.92 for the digital Brix refractometer, respectively. All four refractometers were useful for assessing FTPI in Chianina calves. However, the digital Brix had the highest combined diagnostic accuracy for FTPI. The on-farm use of refractometers to assess FTPI can become part of routine monitoring of the colostrum management program in beef–suckler calf herds. Highlights: The cutoff values were 51 and 52 g/L for the digital and optical serum total protein refractometers, respectively. The digital Brix refractometer was the most accurate for the detection of calves with inadequate transfer of passive immunity.